1993
DOI: 10.1046/j.1468-2982.1993.1304261.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Adaptation in Migraineurs with Chronic Daily Headache

Abstract: Ergotamine and analgesic misuse are now recognized as causes of chronic daily headache and the condition responds well to drug withdrawal with reduced headache frequency. In this study, we have investigated whether medication misuse is associated with an alteration in membrane transduction which is sensitive to drug withdrawal. This was carried out by assay of the thrombin-stimulated generation of inositol phosphates in platelets from 12 migraine patients with chronic daily headache and analgesic misuse, 7 mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…the serotoninergic system is modulated by the intake of different classes of analgesics which will lead to alterations of the antinociceptive serotoninergic pathway and central sensitization [9-16]. Other mechanisms proposed involve the NMDA-receptor [17], the opioid- system [18], and alterations in membrane transduction [19]. …”
Section: Introductionmentioning
confidence: 99%
“…the serotoninergic system is modulated by the intake of different classes of analgesics which will lead to alterations of the antinociceptive serotoninergic pathway and central sensitization [9-16]. Other mechanisms proposed involve the NMDA-receptor [17], the opioid- system [18], and alterations in membrane transduction [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Srikiatkhachorn et al 23 suggested that the excessive use of SM could lead to an upregulation of central serotonergic receptors suppressing therefore the function of serotonergic pathways involved in central pain modulation. Hering et al 24 observed an increase in blood level of serotonin after withdrawal of overused SM in chronic daily headache patients. In addition, these authors analyzed the platelet membrane transduction of patients with daily headache suggesting that the overuse of SM would result in a modification of this process, possibly playing a role in such a headache pattern modification 25 .…”
Section: Methodsmentioning
confidence: 97%
“…This finding is in accordance with the observation that chronic analgesic consumption has a significant effect on signal transduction mechanism. In 1993, Hering et al [36] found that analgesic withdrawal can induce a normalization of the abnormally upregulated thrombin-stimulated inositol phosphate production in platelet in a timedependent manner. They also found that this downregulation correlated with the improvement of headache.…”
Section: Dysfunction Of Central Serotonin System As a Mechanism Of Anmentioning
confidence: 99%